Penatalaksanaan Aspirasi Benda Asing pada Pasien Pediatrik - wullur, caroline; Rasman, Marsudi (Majalah Anestesia dan Critical Care, 2014)
Aspirasi benda asing adalah kejadian yang sering terjadi terutama pada populasi anak-anak. Kejadian ini dapat membahayakan nyawa sehingga diperlukan tindakan ekstraksi benda asing tersebut dengan segera. Diagnosis pasti dapat terhambat terutama bila dari anamnesa tidak spesifik, ketika orang tua tidak mampu menyadari pentingnya gejala, atau bahkan ketika temuan klinis dan radiologis tidak spesifik atau terlewatkan oleh dokter. Aspirasi bahan organik dapat menyebabkan peradangan mukosa saluran napas berat. Jika bahan organik tidak segera diekstraksi, peradangan kronis akan menyebabkan terbentuknya jaringan granulasi di sekitar benda asing, yang pada akhirnya dapat menyebabkan infeksi paru-paru, baik pneumonia maupun abses. Pada kejadian aspirasi benda asing, tidak jarang pasien datang dengan komplikasi sekunder, seperti demam terus-menerus, “asma”, atau pneumonia berulang untuk waktu yang lama. Pada tulisan ini akan diulas mengenai kejadian aspirasi-benda asing, berbagai samaran klinisnya, tata laksana ekstraksi dan anestesi yang tersedia, serta langkah-langkah yang dapat dilakukan untuk mencegah aspirasi. Kata kunci: Aspirasi, benda asing, bronkoskopi Foreign-body aspiration is a relatively common occurrence in children. It may present as a life-threatening event that necessitates prompt removal of the aspirated material. However, the diagnosis may be delayed when the history is atypical, when parents fail to appreciate the significance of symptoms, or when clinical and radiologic findings are misleading or overlooked by the physician. Aspiration of organic matter causes severe airway mucosal inflammation. If the organic matter is not promptly removed, chronic inflammation leads to the development of granulation tissue around the foreign body, which may ultimately present as a lung infection. In this setting, it is not uncommon to treat patients for secondary complications, such as persistent fever, “asthma,” or recurrent pneumonia for long periods. Here we review the incidence of foreign-body aspiration, its various clinical presentations, its management including anesthesia techniques, and measures we can do to prevent future aspirations. Key words: Aspiration, foreign body, bronchoscopy Reference Kalyanappago VT, Kulkarni NH, Bidri LH. Management of tracheobronchial foreign body aspirations in paediatric age group – A 10 year retrospective analysis. Indian J. Anaest 2007; 51(1): 20–23 Fidkowski C.W, Zheng H, Firth PG, The anaesthetic considerations of tracheobronchial foreign body in children: a literature review of 12.979 cases. Anaest Analg. 2010; 111(4): 1016–25 Roberts S and Thomington RE, Pediatric bronchoscopy. Contin educ anaesth crit care pain. 2005; 5 (2): 41 ̶ 44 Cote C, Lerman J, Anderson B. Otolaryngiologic procedure. Chapter 31 Page 657 ̶ 681. In: A practice of anesthesia for infants and children. 5th edition. Philadephia: Saunders Elsevier Publishing; 2013. Weir PM. Foreign Body Aspiration. Chapter 27, Pages 163–166. In: Problems in Anaesthesia: Paediatric Anaesthesia. Stoddart PA, Lauder GR (editors). London: Taylor and Francis Books Ltd; 2004 Naragund AI, Mudhol RS, Harugop AS, Patil PH, Hajare PS, Metgudmath VV. Indian J Otolaryngol Head Neck Surg. 2014; 66(S1): 180–5 A-Kader HH. Foreign body ingestion: children like to put objects in their mouth. World J Pediatr. 2010, 6(4): 301 ̶ 310 Seth D, Kamat D, Pansare M. Foreign body aspiration, a guide to early detection, optimal therapy. Consultant 360 for Pediatricians. 2007; 6(1) Farrell PT. Rigid Bronchoscopy for foreign body removal: anaesthesia and ventilation. Paediatric Anaesthesia 2005; 14: 84–89. American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care: Pediatric Basic Life Support. Circulation. 2005;112:156–166